(untitled) (The International Journal for Scientific Research, 2025)
This study aims to explore the role of innovative management in empowering entrepreneurial start-up projects, using the Entrepreneurship Center at King Khalid University as a case study. The research responds to the growing need to enhance innovation ecosystems within Saudi universities to support the transition towards a competitive knowledge-based economy. A qualitative methodology was adopted, where data were collected through an open-ended questionnaire, semi-structured interviews, and document analysis of the center’s official publications. This approach allowed for capturing the real perceptions of beneficiaries, employees, and experts regarding the nature of the center’s innovative management practices and their impact on the entrepreneurial journey. The findings revealed that while the center implements several innovation oriented practices - such as workshops, incubation programs, and entrepreneurship competitions - these initiatives vary in terms of maturity and integration. Challenges were identified, including limited financial and human resources, weak external networking, and the lack of sustainable support programs for post-incubation phases. The results emphasized that innovative leadership, knowledge management, organizational flexibility, fostering an innovation culture, and external partnerships are critical dimensions that significantly enhance the center’s capacity to empower emerging projects and ensure their sustainability. Based on the findings, the study recommends adopting more flexible management policies, expanding partnerships with the private sector, and establishing specialized acceleration programs within the university to transform the center into a genuine innovation hub. This research contributes to enriching the Arabic literature on university entrepreneurship ecosystems and offers an analytical model that can be applied to other academic settings to foster innovation and empower young entrepreneurs.